2016
DOI: 10.15255/cabeq.2015.2308
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Correlation of Phase Diagram Data of Hydrophilic Alcohols (1-Propanol/2-Propanol) + Salts (Na2SO4/(NH4)2SO4/NH4NO3) + Water Systems

Abstract: Binodal data and the ternary liquid-liquid equilibria (LLE) was experimentally determined at 298.15 K for hydrophilic alcohols (1-propanol or 2-propanol) + salts (Na 2 SO 4 , (NH 4) 2 SO 4 or NH 4 NO 3) + water systems. The salting-out and the phase-forming abilities of the salts and alcohols for the investigated ATPSs were discussed. The salting-out abilities of the investigated salts follow the order Na 2 SO 4 > (NH 4) 2 SO 4 > NH 4 NO 3 , which can be indicated by the location of the binodal curves plotted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Up to now, various researchers were carrying out the study of ATPS by using a phase diagram in which they used some models and equations to correlate the binodal and tie line in liquid-liquid equilibria (LLE) [10][11][12][13][14][15][16]. In recent years, several researchers focused on the measurement and investigation of thermodynamics of ATPSs composed of an aqueous solution of a short chain aliphatic alcohol in the presence of an electrolyte [10,11,[17][18][19][20][21]. However, the detailed study of molecular interactions responsible for phase separation is not reported in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, various researchers were carrying out the study of ATPS by using a phase diagram in which they used some models and equations to correlate the binodal and tie line in liquid-liquid equilibria (LLE) [10][11][12][13][14][15][16]. In recent years, several researchers focused on the measurement and investigation of thermodynamics of ATPSs composed of an aqueous solution of a short chain aliphatic alcohol in the presence of an electrolyte [10,11,[17][18][19][20][21]. However, the detailed study of molecular interactions responsible for phase separation is not reported in detail.…”
Section: Introductionmentioning
confidence: 99%
“…This can result in having constant effects on the environment. , The environmental protection organization (EPA) has reported the acceptable value of these particles as about 1 mg/L in wastewater. Antibiotics are less biodegradable, highly toxic, carcinogenic, and allergenic, and cause the growth of antibiotic-resistant bacteria. Due to tetracycline’s high hydrophobicity (high tendency to form hydrogen bonds with water) and its low volatility, these characteristics make it more challenging to treatment …”
Section: Introductionmentioning
confidence: 99%
“…Also, the cost-effectiveness issue has made adsorption and oxidation methods out of usage. Using membranes might cause damage from the different organic solvents. Solid-phase extraction or matrix solid-phase dispersion methods usually take a while and have a low selectivity factor.…”
Section: Introductionmentioning
confidence: 99%